An Identification of Conceptual and Procedural Understanding: Study on Preservice Secondary Mathematics Teacher - Klau, Kondradus Yohanes; Siahaan, Meiva Marthaulina Lestari; Simarmata, Justin Eduardo (Universitas Islam Raden Intan Lampung, INDONESIA, 2020)
Preservice mathematics teachers (PSMTs) need to master teaching material besides pedagogical competence. This knowledge is a combination of conceptual and procedural knowledge. Teachers should possess the ability to explain a concept, the reason for the concepts used, and the relationship among several concepts clearly and effectively to identify why the concept is used. This study aimed to identify the conceptual and procedural knowledge of PSMTs in Linear Algebra courses. Data collection was carried out through tests and interviews. The interview was conducted with several participants to clarify their test answers. The participants' interview answers revealed that they had difficulty in choosing the proper concept answering modified questions. Also, the participants tried to answer the question using a procedural approach. According to the findings, it is vital to construct appropriate teaching materials appropriate for the learning objective and material map concept.